2004
DOI: 10.1097/01.chi.0000134491.42807.a3
|View full text |Cite
|
Sign up to set email alerts
|

Inhalant Abuse and Dependence Among Adolescents in the United States

Abstract: Objective-To examine the patterns of inhalant use and correlates of the progression from inhalant use to abuse and dependence among adolescents aged 12 to 17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
109
2
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 34 publications
4
109
2
3
Order By: Relevance
“…Inhalation of nitrites also impairs immune functioning that suppresses resistance to infection and actively promotes viral replication and tumor growth (Soderberg, 1998). Several studies have suggested that youthful inhalant use is highly associated with alcohol abuse or dependence, the use of multiple illicit drugs, and injection drug use (Bennett et al, 2000;Dinwiddie et al, 1991;Schütz et al, 1994;Wu et al, 2004Wu et al, , 2005aWu et al, , 2005b. Early inhalant use is also associated with later initiation of heroin and other opiates (Johnson et al, 1995;Storr et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Inhalation of nitrites also impairs immune functioning that suppresses resistance to infection and actively promotes viral replication and tumor growth (Soderberg, 1998). Several studies have suggested that youthful inhalant use is highly associated with alcohol abuse or dependence, the use of multiple illicit drugs, and injection drug use (Bennett et al, 2000;Dinwiddie et al, 1991;Schütz et al, 1994;Wu et al, 2004Wu et al, , 2005aWu et al, , 2005b. Early inhalant use is also associated with later initiation of heroin and other opiates (Johnson et al, 1995;Storr et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Early inhalant use is also associated with later initiation of heroin and other opiates (Johnson et al, 1995;Storr et al, 2005). A recent study of a national sample of American adolescents aged 12 to 17 found that 11% of past year inhalant users met the criteria for an inhalant use disorder in the past year (Wu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations